Investigating nurses' knowledge and attitudes about delirium in older persons: a cross-sectional study - Maria Papaioannou; Evridiki Papastavrou; Christiana Kouta; Haritini Tsangari; Anastasios Merkouris (BMC, 2023)
Abstract Introduction Delirium is the most common emergency for older hospitalized patients that demands urgent treatment, otherwise it can lead to more severe health conditions. Nurses play a crucial part in diagnosing delirium and their competencies facilitate the appropriate treatment and management of the condition. Aim This study aims to enhance the understanding of delirium care by exploring both knowledge and attitudes of nurses toward patients in acute care hospital wards and the possible association between these two variables. Method The Nurses Knowledge of Delirium Questionnaire (NKD) and the Attitude Tool of Delirium (ATOD) that were created for the said inquiry, were disseminated to 835 nurses in the four largest Public Hospitals of the Republic. These tools focused particularly on departments with increased frequency of delirium (response rate = 67%). Results Overall nurses have limited knowledge of acute confusion/delirium. The average of correct answers was 42.2%. Only 38% of the participants reported a correct definition of delirium, 41.6 correctly reported the tools to identify delirium and 42.5 answered correctly on the factors leading to delirium development. The results of the attitudes' questionnaire confirmed that attitudes towards patients with delirium may not be supportive enough. A correlation between the level of nurses' knowledge and their attitude was also found. The main factors influencing the level of knowledge and attitudes were gender, education, and workplace. Conclusion The findings of this study are useful for the international audience since they can be used to develop and modify educational programmes in order to rectify the knowledge deficits and uninformed attitudes towards patients with delirium. The development of a valid and reliable instrument for the evaluation of attitudes will help to further assess nurses' attitudes. Furthermore, the results are even more important and useful on a national level since there is no prior data on the subject area, making this study the first of its kind.